Istikhdamu Namuzaj at-Taklimut taawuniy Biuslubi ‎Group investigation Litaqiyati Qudrati Tullab Fi tallumi ‎Maharah Al-Qiraah Lissafi Tsamin Fi Al-Madrasah Al-‎Islamiyah Al-Hukumiyah 4 Agam‎ - Okriza Febria; Rehani Rehani (Lisaanuna Ta`lim Al-Lughah Al-Arabiyah: Jurnal Pendidikan Bahasa Arab, 2023)
The main problem in this research is “What is the effect of using the ‎cooperative edycation model using the Group Investigation method to ‎improve student ability to teach the reading skill for the eight grade in ‎the Islamic Hight SchoolAgam?”. Before using the Group Investigation ‎model to detect the use of the Group Investigation model on student ‎ability to read in Islamic Hight School 4 Agam in the eight semester, to ‎identify the result of learning the reading skill using the Group ‎Investigation model for eight grade in the Islamic Hight School 4 Agam. ‎The research method used is quantitative study approach that is quasi ‎eksperimen mothod and analytic data use SPSS. The result showed the ‎Group Investigation learning model had an effect on improving student ‎Maharah Qiraah abilities at MTsN 4 Agam, this was evidenced by the ‎average pretest score of the experimental class being higher than the ‎average control score. The average value of the experimental class is ‎‎94,80 and the control class is 64,23. and based on result of Paired ‎Sample T test, T table -32,510 bigger than T count -9,819‎